ON THE SIGNIFICANCE OF CREATIVE AND SOCIAL COMPETENCES IN MUSIC EDUCATION - Ergashev Murodbek Ikromovich (Galaxy International Interdisciplinary Research Journal, 2022)
The article is devoted to topical issues related to the importance of creative and social competencies in music education.